USE AND QUALITY ASSESSMENT OF YOUTUBE VIDEOS ON THE MOST COMMON DERMATOLOGIC DISORDEERS: A SYSTEMATIC REVIEW - Aleksandra Kujach; Julia Kropidłowska (International Journal of Innovative Technologies in Social Science, 2025)
This systematically conducted narrative review explores the quality and reliability of dermatology-related information available on YouTube. A comprehensive literature search of PubMed and Scopus (up to November 2024) identified 8,521 records, of which 25 studies met the inclusion criteria addressing six major dermatologic topics: hidradenitis suppurativa, acne vulgaris, atopic dermatitis, psoriasis, skin cancer, and Mohs micrographic surgery. Across conditions, YouTube was found to be a popular platform for health information seeking, yet most videos were created by non-medical individuals and exhibited low educational quality based on validated instruments such as DISCERN, JAMA, and the Global Quality Scale. Common issues included incomplete, misleading, or unreferenced information, with misleading content often attracting higher engagement than professional materials. While videos produced by healthcare professionals were generally more accurate, they represented a minority and achieved limited visibility. Despite YouTube’s potential for public health education, current dermatology-related content often fails to meet evidence-based standards. These findings highlight the urgent need for dermatologists and professional organizations to create and promote high-quality, comprehensible, and reliable video content to improve public understanding, counter misinformation, and support informed patient decision-making.